KALIBRASI SENSOR TEMPERATUR DENGAN METODA PERBANDINGAN DAN SIMULASI - Cecep Sulaeman; Kusnadi kusnadi (Jurnal Poli-Teknologi, 2011)
PT 100 temperature sensor calibration and Thermocouple can use the method of comparison or simulation. Method of comparison used by a standard calibration comparing with the source of ice cubes and boiling water to the Controller E5EK Omron Digital Indicator. The temperature measurement data is calculated through the four (4) the uncertainty is the uncertainty of the standard, master, joint, and stretching. Simulation results of the measurement data are made with data on indicators by Omron E5EK DigitalController InsL and InsH seek to determine the nominal value of the temperature. Keywords: Calibration, Sensor, Comparison, Simulation ABSTRAK Kalibrasi sensor temperatur PT 100 dan Thermocouple dapat menggunakan metoda perbandingan atau simulasi. Metoda perbandingan digunakan dengan cara membandingkan kalibrator standar berupa dengan sumber es batu maupun Air mendidih terhadap Indikator Digital Controller E5EK Omron. Data pengukuran Temperatur dihitung melalui empat (4) ketidakpastian yaitu ketidakpastian standar, master, gabungan dan terentang. Hasil data pengukuran dibuat Simulasi dengan data pada Indikator DigitalController E5EK Omron dengan cara mencari InsL dan InsH untukmenentukan nilai nominal temperatur. Kata kunci: Kalibrasi, Sensor, Perbandingan, Simulasi.